2022
DOI: 10.1155/2022/8373697
|View full text |Cite
|
Sign up to set email alerts
|

Seven Months after Mild COVID-19: A Single-Centre Controlled Follow-Up Study in the District of Constance (FSC19-KN)

Abstract: Importance. Viral infections can lead to prolonged recovery and secondary diseases among the survivors. Therefore, the management of post-coronavirus infectious disease 2019 (COVID-19) patients needs to be planned efficiently based on significant data. Despite numerous follow-up studies, there still is a lack of knowledge in this field. Objective. The primary aim of the study was to investigate the rate of hospitalization and admission diagnoses in severe acute respiratory syndrome coronavirus type 2 (SARS-CoV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
2

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 39 publications
0
11
0
2
Order By: Relevance
“…On the other hand, an Italian study stratifying 75 PCS patients by Covid-19 symptom load reported mostly unimpaired 6MWD, even in the severe symptoms group [ 34 ]. Another study comparing PCS patients to Covid-19 negative patients matched by sex, age and cardiovascular profile also observed similar performance in 6MWD [ 35 ]. A comprehensive study on all confirmed cases with desaturated oxygen below 94% in Iceland drew a more distinct picture with lowered 6MWD observed only in patients treated in intensive care during Covid-19 [ 36 ].…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…On the other hand, an Italian study stratifying 75 PCS patients by Covid-19 symptom load reported mostly unimpaired 6MWD, even in the severe symptoms group [ 34 ]. Another study comparing PCS patients to Covid-19 negative patients matched by sex, age and cardiovascular profile also observed similar performance in 6MWD [ 35 ]. A comprehensive study on all confirmed cases with desaturated oxygen below 94% in Iceland drew a more distinct picture with lowered 6MWD observed only in patients treated in intensive care during Covid-19 [ 36 ].…”
Section: Discussionmentioning
confidence: 76%
“…Furthermore, other follow-up studies at various time points after Covid-19 observed improvement of physical performance and to some extent of typical PCS symptoms as a function of time rather than rehabilitation [ 30 ]. While controlled trials are exceedingly rare, a study matching confirmed Covid-19 cases to patients without Covid-19 but similar other risk factors observed no differences in standard assessments such as 6MWD [ 35 ]. Hence, we cannot verify that the observed improvement was in fact caused by the rehabilitation program alone.…”
Section: Discussionmentioning
confidence: 99%
“…The meta-analysis of the five studies reporting the EQ-5D indicated a small reduction in overall quality of life between individuals with confirmed SARS-CoV-2 infection versus controls at six to 24 months follow-up, although heterogeneity was very high (mean difference in EQ-5D scale −5.28 (95% confidence interval −7.88 to 2.68); I 2 =93.81%; figure 2). [32][33][34][35][36] One small study with 113 predominantly male (86%), working age (mean 39 (standard deviation 9)) participants provided outlier results in this meta-analysis indicating lower quality of life in individuals with documented symptomatic infection versus noninfected individuals. 37 Nonetheless, when pooling studies with different scales assessing subdomains of quality of life, we found little to no difference, for example, for mental health (Hedges's g −0.07 (95% confidence interval −0.61 to 0.47)) and for physical health (−0.31 (−1.25 to 0.63), figure 3).…”
Section: Quality Of Lifementioning
confidence: 90%
“…Quality of life in covid-19 cases versus controls of studies reporting EQ-5D [32][33][34][35][36]. Symptomatic and asymptomatic groups of Pell and colleagues36 were merged for the analysis.…”
mentioning
confidence: 99%
“…Частота госпитализаций в обеих группах была низкой и сопоставимой (2,4% в группе пациентов, перенесших COVID-19, против 2,9% в контрольной группе). Однако анализ показал снижение КЖ по шкале EQ-5D-5L у пациентов, перенесших COVID-19 (средние значения VAS 83,6 ± 15,2 против 88,6 ± 12,4 мм в группе контроля, р < 0,05) [32].…”
Section: качество жизни у пациентов с постковидным синдромомunclassified